Cytokine profiling and post‐transfusion haemoglobin increment in patients with haematological diseases. Issue 7 (29th August 2018) - Wendelbo, Øystein; Opheim, Elin Netland; Egil Eide, Geir; Hervig, Tor; Felli Lunde, Turid Helen; Bruserud, Øystein; Mollnes, Tom Eirik; Reikvam, Håkon
Abstract : Background and Objectives: In a previous pilot study, we demonstrated significantly lower haemoglobin (Hb) increment after red‐blood‐cell (RBC) transfusions in febrile patients compared to patients without fever. The aim of this study was to examine associations between inflammatory mediators and post‐transfusion haemoglobin increment in patients with haematological diseases. Materials and Methods: Twenty‐seven patients (eight women, 19 men), median age 56 years receiving RBC transfusion, were included in the study. Hb increment per unit transfused was corrected for estimated patient blood volume and the amount of Hb transfused. A wide spectrum of inflammatory mediators was determined by multiplex technology. Association between post‐transfusion haemoglobin increment, plasma inflammatory mediators and patient characteristics was analysed using a mixed linear regression model. Results: Febrile patients had significantly lower corrected Hb increment, significantly increased values of IL‐6, IL‐8, IL‐10 and G‐CSF, significantly reduced levels of CCL5 and CXCL10, and significantly higher pretransfusion levels of CRP. There was a significant association between pretransfusion CRP levels and corrected Hb increment for the whole patient cohort, but not within each of the two groups. Results demonstrated an association between haemoglobin increment, fever and inflammatory mediators. Febrile patients had a significantly lower corrected Hb increment compared to nonfebrile patients, when adjusting for mediators. When fever was kept constant, a significant negative association between haemoglobin increment and the proinflammatory mediators IL‐6 and IL‐8 was observed. Conclusion: Both fever and the inflammatory mediators IL‐6 and IL‐8 were negatively associated with post‐transfusion haemoglobin increment.